REACTION TO THE BLACK CITY AS A CAUSE OF MODERN CONSERVATISM: A Case Study of Political Change in Ohio, 1932–2016. (19th August 2022) - Hackworth, Jason
Abstract: Social scientists in a variety of fields have long relied on economic-structuralist theories to understand the ascendance and hegemony of the modern Conservative Movement in the United States. In the materialist theory of political change (MTPC), structural crisis in the 1970s destabilized Keynesian-managerialism, and paved the way for neoliberalism. Key weaknesses of this approach include its relatively aspatial scope—comparatively less attention to the spatial variation of neoliberalism's popularity—and its demotion of other elements of the Conservative Movement into a veritable super-structure of secondary movements. This paper offers a "racial amendment" to the MTPC, and an application to electoral geographies in the state of Ohio since 1932. This amendment synthesizes group threat theory, critical historiography, and Du Boisian theories of Whiteness to suggest that the growing influence of suburban conservatism is not reducible simply to class interest.